Regional Risk Associated with the Transport of hazardous Materials - Nardini, L. (2003)
An increasing concern over the level of risk associated with hazardous materials transportation has led international efforts to focus on risk assessment at regional level. Following this trend, the aim of this work is to review the latest procedures for analysing the regional risks resulting from hazardous materials transportation by means of road and rail. In particular, two methodologies are reviewed and discussed, a method recently developed at Swiss Federal Institute of Technology [1] and the strategy outlined by CCPS [2]. The extent of these methodologies has been explored in order to find their advantages and disadvantages. As a case study this paper considers the transport of methanol from its production site to the port where it is going to be stored, obtaining risk results using at least one of the above mentioned methodologies.